Altered spaces: new ways of seeing and envisioning nature with Minecraft. Issue 3 (27th May 2022) - McNally, Brenda; de Andrade, Bruno
Abstract : The climate crisis has inspired youth-led activism across the world and young people now lead global campaigns and political protest on climate justice. However, aside from news media coverage of youth activism and the attendant focus on young people's hand-drawn protest placards, relatively little is known about young people's views on the actions needed to respond to the climate crisis or how they imagine environmentally-sustainable futures. This visual essay addresses that lacuna by exploring young people's ideas about local climate actions. The images selected for consideration were created using Minecraft, the 3D block-building visualisation game, at workshops held in Ireland. Young people and their families were invited to create environmentally-sustainable futures at Minecraft workshops. Exploring these 3D designs as images, the essay documents young people's visual representations of desirable climate actions and reflects on these Minecraft images to shed light on how young people envision alternative climate futures. These collective visions, or climate imaginaries, are powerful indicators of what young people imagine is possible in the future. In doing so, they present an alternative to the mainstream news and entertainment media preoccupation with dystopian constructions of the climate crisis. They also highlight the power of Minecraft as a visual medium to open up new ways of seeing nature and of envisioning nature-society relations. The selected images were also exhibited as part of the CLIMATE LOOK Lab 2022 held at the Open Eye Gallery, Liverpool. The gallery invited researchers, community groups and artists to use the gallery as a lab space to engage visitors with our changing environment and to explore how images can change the visual narrative on climate change.